Assessment of teacher knowledge across countries: A review of the state of research - Delaney, Seán (Springer, 2012)
This review presents an overview of research on the assessment of mathematics teachers’ knowledge as one of the most important parameters of school quality. Its focus is on comparative and international studies that allow for analyzing the cultural dimensions of teacher knowledge. In a first step, important conceptual frameworks underlying comparative studies of mathematics teachers' knowledge are summarized. Then, key instruments designed to assess the content knowledge and pedagogical content knowledge of future and practicing mathematics teachers in different countries are described. Core results from comparative and international studies are documented, including what we know about factors influencing the development of teacher knowledge and how the knowledge is related to teacher performance and student achievement. Finally, we discuss the challenges connected to cross-country assessments of teacher knowledge and we point to future research prospects.
The final publication is available at http://www.springerlink.com/content/w7214t0124j75835/. This version may differ in minor ways from the published version.
Keywords: Mathematics teacher education; comparative study; Mathematics content knowledge; Mathematics pedagogical content knowledge; large scale assessment